Analisis pola argumentasi siswa dalam menyelesaikan soal permutasi dan kombinasi - Hasanul Anshori, Hasanul Anshori; Parhaini Andriani, Parhaini Andriani (Jurnal of Math Tadris, 2021)
Argumentation is a person's way to face every question, issue and argue in the face of every problem. Argumentation is very necessary to know the understanding of students' concepts and so that students can explain logically the appropriate stages of completion to solve problems. This study aims to describe the pattern of argumentation used by students in solving permutations and combinations problems. This type of research is descriptive qualitative. The research subjects were 3 students of class XI IPA at MA Darul Aitam Jerowaru which consisted of 1 student with high math ability, 1 student with moderate math ability, and 1 student with low math ability. Sampling was done by using purposive sampling type quota sampling. Data collection techniques used written tests and interviews, then analyzed based on indicators of student argumentation patterns in solving permutations and combinations. Based on this, the argumentation pattern used in this study is a combination of Tulmin's argumentation pattern and Mc. Neill & Karajicik's argumentation pattern, namely, data, claim, evidence, reasoning and rebuttal. The results of this study are students with high mathematical abilities have a pattern of argumentation, namely, data, claims, evidence, which are given correctly. Students with moderate ability have argumentation patterns, namely, data, claim, reasoning, and rebuttal, which are given correctly and students with low mathematical abilities have argumentation patterns, namely, data, claim, and rebuttal, which are given correctly.